Perbedaan Antara Parkir Kapal Dan Kendaraan Serta Sistem Operasinya - Apriyanto Budhi Wibowo; Nailis Sa’adah (Jurnal Sipil Terapan, 2023)
For a Mall itself has a strategic location factor supported by road network access, visitors, exhibition activities, consumer needs as well as market demand, existing entertainment services, as well as those from the Mall itself. An advantage in itself will be the demand for a market and its management which may be felt to have more carrying capacity. From the development of Mall itself, which pampers the needs of a certain time. From the needs of a market obtained from exports or imports. As well as distances that are easy to reach by the people of Semarang themselves either via public transportation or private vehicles.